1983
DOI: 10.1136/bjo.67.3.153
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo and disorders of the retinal pigment epithelium.

Abstract: SUMMARY The association of vitiligo with inflammation of the uveal tract is well established. The relationship between vitiligo and hypopigmentation and/or degeneration of the retinal pigment epithelium (RPE) not secondary to ocular inflammation has not been adequately investigated. Sixty (27%) of 223 consecutive patients with vitiligo were found to have some evidence of RPE hypopigmentation ranging from mild, focal areas of involvement in most cases to extensive RPE degeneration with a retinitis pigmentosa-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…Eye findings were investigated in patients with cutaneous vitiligo, but the results were limited. Posterior uveitis, sympathetic ophthalmia, and RPE atrophy were reported in vitiligo . Uveal inflammation related to those findings may suggest that inflammatory reaction may play a role in the etiopathogenesis of vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…Eye findings were investigated in patients with cutaneous vitiligo, but the results were limited. Posterior uveitis, sympathetic ophthalmia, and RPE atrophy were reported in vitiligo . Uveal inflammation related to those findings may suggest that inflammatory reaction may play a role in the etiopathogenesis of vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…Antithyroid antibodies were detected in 13 patients (not all symptomatic for thyroid dysfunction). 28,29 As vitiligo affects all active melanocytes, auditory and ocular problems may result in patients with vitiligo. We believe that the significant number of vitiligo patients with atopic dermatitis in our study merely reflects the high prevalence of atopic dermatitis observed in the general population in Tunisia.…”
Section: Discussionmentioning
confidence: 99%
“…Large studies suggest that choroidal pigmentary changes occurring in the presence of vitiligo can be ascribed to uveitis in many cases, although in some no evidence of inflammation could be found. [1][2] Only a small number of cases have been reported with widespread hypopigmentation of both choroid and retinal pigment epithelium (RPE). [1][2][3] Our two patients with vitiligo had extensive choroidal hypopigmentation without signs or a previous history of ocular inflammation.…”
mentioning
confidence: 99%
“…[1][2] Only a small number of cases have been reported with widespread hypopigmentation of both choroid and retinal pigment epithelium (RPE). [1][2][3] Our two patients with vitiligo had extensive choroidal hypopigmentation without signs or a previous history of ocular inflammation. They both had normal visual function, and additional fluorescein angiogram and electrodiagnostic tests in case 1 were normal.…”
mentioning
confidence: 99%
See 1 more Smart Citation